Priyanka2011 wrote:

Hai.. sorry for the bad usage of syntax.. yeah what you have inferred is absolutely right !

[(x+4)^2]^(1/2) = 3

If the problem is as above, how is x=-7 ( i get the other part being simple ! )

Well, there are a few ways to approach this ---- the straightforward algebraic way would be to solve for x -----

[(x+4)^2]^(1/2) = 3

undo the power of 1/2 by squaring both sides

(x+4)^2 = 9

take a square root of both sides, remembering the +/- sign

x+4 = +/-3, which means x = -1 and x = -7

The equation u^2 = 9 must have two solutions, u = +3 and U = -3, because (3)^9 and also (-3)^2 = 9

Another way to go about it is to plug in the solution x = -7 to verify that it satisfies the equation.

[(x+4)^2]^(1/2) = [(-7+4)^2]^(1/2) = [(-3)^2]^(1/2) = 9^(1/2) = 3

so, x = -7 checks out --- it is a valid solution for this equation.

Notice, even though u^2 = 9 has two solutions, the positive root and the negative root, the expression 9^(1/2) has only one output, just the positive root.

Does all this make sense? Please let me know if you have any further question.

Mike

_________________

Mike McGarry

Magoosh Test Prep